Reorienting Heritage: Poetic Exchanges between Suquṭra and the Gulf - Nathalie M. Peutz (Revue des Mondes Musulmans et de la Méditerranée)
Two historical events that occurred on the Yemeni island of Suquṭra — the conquest of the island by “Christians” in the 9th century and the execution of a group of Suquṭran elites in 1974 —are made relevant today in poetry exchanges between the island residents and the Suquṭran expatriate community in the Gulf. Through these poems and the context of their transnational circulation, the Suquṭran Diaspora is vying for the ability to determine Suquṭri heritage at a time that international, state, and local actors are advancing competing claims for that right. This article examines some of the various ways in which these claims to Suquṭri heritage and their implications for Suquṭri identity are being enunciated.